Disaster management - Gupta, Harsh K. (Hyderabad : Distributed by Orient Longman, 2003)
This book contains seven chapters, each dealing with one major natural disaster encountered in our country. Each of the authors is an expert in that particular field. The outstanding contribution of this book is that it not only deals with the forecasting and description of the various natural disasters, but also stresses the management aspect, exhaustively detailing the necessary steps that need to be taken to deal with the fallout in the wake of these disasters. The book also describes the advances in remote sensing and the state-of-the-art technology available in India for the monitoring and prediction of these phenomena. It also draws up a comprehensive warning system to be implemented, in order to minimize the extensive losses to life and property that occur year after year.
Includes bibliographical references and index.
Keywords: Natural disasters -- India; Hazardous geographic environment -- India; Emergency management -- India